Transcriptome profiling of gene expression during immunisation trial against Fasciola hepatica: Identification of genes and pathways involved in conferring immunoprotection in a murine model (2017)
Background: Fasciolosis remains a significant food-borne trematode disease causing high morbidity around the world and affecting grazing animals and humans. A deeper understanding concerning the molecular mechanisms by which Fasciola hepatica infection occurs, as well as the molecular basis involved in acquiring protection is extremely important when designing and selecting new vaccine candidates. The present study provides a first report of microarray-based technology for describing changes in the splenic gene expression profile for mice immunised with a highly effective, protection-inducing, multi-epitope, subunit-based, chemically-synthesised vaccine candidate against F. hepatica. Methods: The mice were immunised with synthetic peptides containing B- and T-cell epitopes, which are derived from F. hepatica cathepsin B and amoebapore proteins, as novel vaccine candidates against F. hepatica formulated in an adjuvant adaptation vaccination system; they were experimentally challenged with F. hepatica metacercariae. Spleen RNA from mice immunised with the highest protection-inducing synthetic peptides was isolated, amplified and labelled using Affymetrix standardised protocols. Data was then background corrected, normalised and the expression signal was calculated. The Ingenuity Pathway Analysis tool was then used for analysing differentially expressed gene identifiers for annotating bio-functions and constructing and visualising molecular interaction networks. Results: Mice immunised with a combination of three peptides containing T-cell epitopes induced high protection against experimental challenge according to survival rates and hepatic damage scores. It also induced differential expression of 820 genes, 168 genes being up-regulated and 652 genes being down-regulated, p value <0.05, fold change ranging from -2.944 to 7.632. A functional study of these genes revealed changes in the pathways related to nitric oxide and reactive oxygen species production, Interleukin-12 signalling and production in macrophages and Interleukin-8 signalling with up-regulation of S100 calcium-binding protein A8, Matrix metallopeptidase 9 and CXC chemokine receptor 2 genes. Conclusion: The data obtained in the present study provided us with a more comprehensive overview concerning the possible molecular pathways implied in inducing protection against F. hepatica in a murine model, which could be useful for evaluating future vaccine candidates. © 2017 The Author(s).